ANALISIS SPASIAL TEKANAN PENDUDUK TERHADAP LAHAN PERTANIAN DI SUB DAS KEDUANG, KABUPATEN WONOGIRI, JAWA TENGAH - Agus Wuryanta; Pranatasari Dyah Susanti (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2015)
Population pressure on agricultural land is one of the important parameters to determine the level of watershed environment quality. High population pressure on agricultural land in a watershed can lead to land degradation and watershed ecosystems damage. The purpose of research is to calculate and determine the level of population pressure on agricultural land in the sub watershed and in each district in the sub watershed by using Geographic Information System (GIS). Population pressure on agricultural land is calculated by using Soemarwoto's formula (1985). The classification of population pressure on agricultural land is based on the Decree of the Directorate General of Land Rehabilitation and Social Forestry (RLPS,) Ministry of Forestry of Indonesia No. P.04/VSET/2009. The research was conducted in Keduang sub-watershed which is part of water chatchment area of Gajah Mungkur Reservoir in Wonogiri District, Central Java. The results showed that population pressure on agricultural land in Keduang Sub-watershed is categorized as “bad” with the value of 28.978,16. Girimarto, Jatipurno, Jatiroto, Jatisrono and Sidoharjo districts are categorized as “medium”, while Jatiyoso, Kismantoro, Ngadirojo, Nguntoronadi, Purwantoro, Slogohimo and Tirtomoyo districts are categorized as “bad” with the value more than 2.